Energy Absorption of Partially Filled Side Member Subjected to Oblique Crash - Salwani, Mohd Salleh; B. B., Sahari; A., Ali; A. A., Nuraini (Trans Tech Publications, Switzerland, 2014)
This study analyzed the crash performance of partially filled column in comparison to an empty and fully filled side member. Crash simulation is carried out by impacting a car moving at 48 km/hr to a rigid wall at an angle of 30 degrees. It was found that the partially filled side member is capable of absorbing almost the same amount of energy as the fully filled side member at lower mass.